The Water Road : A Narrowboat Odyssey Through England - Gogarty, Paul (London Robson Books, 2000)
To escape the hurry-sickness of modern life, Paul Gogarty...acclaimed travel writer and TV presenter...disappears for 4 months into a maze of canals linking the Thames with the Severn, Mersey and Trent. On this magical journey across the face of backdoor England the author weaves a mesmerising tale packed with drama, hilarious encounters and illuminating reflection as he revels in the canals network's second golden age following more than a century of neglect. The Water Road is both a celebration of a secret England and a powerful personal odyssey, in which the author marks his own rite of passage.
Includes Colored Illustrations, Bibliography and Index.
Keywords: England -- Description and travel